PENGARUH KEPUTUSAN INVESTASI, KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Farmasi yang Terdaftar Di Bursa Efek Indonesia Periode 2009-2016) - Sampurna, Dian Surya; Sari, Mila Novita (JAB (Jurnal Akuntansi & Bisnis), 2018)
This study aims to determine the effect of investment decisions, debt policy, dividend policy, and profitability on firm value. The strategy carried out in this study is an associative strategy and the method chosen is the ex post facto method. The research sample was taken using purposive sampling amounting to 5 companies and the analytical method used was multiple regression analysis. The results showed that investment decisions (PER) and profitability (ROA) had a positive and significant effect on firm value (PBV), debt policy (DER) had a positive and not significant effect on firm value (PBV), and dividend policy (DPR) had a negative effect and not significant to company value (PBV). Furthermore, the results of the coefficient of determination indicate that changes in the value of the company value variable (PBV) are influenced by investment decisions (PER), debt policy (DER), dividend policy (DPR) and profitability (ROA) of 88.1%, while the remaining 11 , 9% is influenced by other factors not included in this study.Â Keywords: PER, DER, DPR, ROA, PBV